Postpartum Patient Perspectives on the US Medicaid Waiting Period for Permanent Contraception - Hartheimer JS; Bullington BW; Berg KA; White K; Boozer M; Serna T; Miller ES; Bailit JL; Arora KS (Open Access Journal of Contraception)
Joline S Hartheimer,1 Brooke W Bullington,2,3 Kristen A Berg,4 Kari White,5 Margaret Boozer,6 Tania Serna,7 Emily S Miller,8 Jennifer L Bailit,9 Kavita Shah Arora10 1Swedish First Hill Family Medicine Residency, Swedish Medical Center, Seattle, WA, USA; 2Department of Epidemiology, Gillings School of Global Public Health, University of North Carolina at Chapel Hill, Chapel Hill, NC, USA; 3Carolina Population Center, University of North Carolina at Chapel Hill, Chapel Hill, NC, USA; 4Center for Health Care Research & Policy; MetroHealth Medical Center at Case Western Reserve University School of Medicine, Cleveland, OH, USA; 5Population Research Center, Steve Hicks School of Social Work, University of Texas at Austin, Austin, TX, USA; 6Department of Obstetrics and Gynecology, University of Alabama at Birmingham, Birmingham, AL, USA; 7Department of Obstetrics and Gynecology, University of California San Francisco, San Francisco, CA, USA; 8Department of Obstetrics and Gynecology, Division of Maternal Fetal Medicine, Warren Alpert Medical School of Brown University, Providence, RI, USA; 9Department of Obstetrics and Gynecology, Case Western Reserve University, Cleveland, OH, USA; 10Department of Obstetrics and Gynecology, University of North Carolina at Chapel Hill, Chapel Hill, NC, USACorrespondence: Kavita Shah Arora, Email Kavita.shah.arora@gmail.comObjective: The Medicaid Consent to Sterilization policy is a known barrier to permanent contraception (PC) fulfillment and is associated with disparities in fulfillment. While physician perspectives regarding the policy are well described, knowledge of how patients with Medicaid seeking PC perceive this waiting period is limited.Study Design: We interviewed 81 participants with a documented desire for PC at discharge from their hospital-based delivery at four medical centers across the United States. Interviews were audio-recorded, transcribed, and analyzed using rapid qualitative methodologies and thematic content analysis.Results: Of the 81 participants interviewed, the 56 participants subject to the mandatory waiting period through insurance status or state residency were included in this analysis. Key positive themes included the role of the waiting period in facilitating minimization of regret, independent decision making, and protection against coercion and bias. Key negative themes included interference with reproductive autonomy, harm to the patient-clinician relationship, and introduction of unwanted doubt into contraceptive decisions. In addition, participants expressed both indifference and nuance when discussing the waiting period, and misinformation about the waiting period was prevalent during interviews. Participants with favorable opinions commonly changed their mind regarding PC, while participants with negative opinions were steadfast in their desires for PC and often experienced PC non-fulfillment.Conclusion: Postpartum patients hold diverse views on the current Medicaid Consent to Sterilization policy’s mandated waiting period. Patient engagement is fundamental when reevaluating and revising this policy to balance supporting autonomous decision-making about PC while protecting against reproductive coercion and regret.Implications: In policy revision discussions, it is important to consider whether a mandated waiting period is the best way to minimize regret and promote autonomy. Revision that accounts for the complexity of patient desires and needs is imperative to achieving the dual goals of minimizing coercion and ensuring autonomously-desired provision.Keywords: contraception, sterilization, Medicaid, health disparities, health policy, reproductive health